2021
DOI: 10.3855/jidc.14316
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 imported cases and severity: expected information from genomic characterization of SARS-CoV-2 strains in Mozambique

Abstract: Introduction: The novel coronavirus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), etiological agent of coronavirus disease 2019 (COVID-19) was first reported in China in December 2019 and spread worldwide. As of March 6th, 2021, there have been 116,670,105 million confirmed cases globally including 2,592,085 deaths. COVID-19 cases have been reported in 219 countries and territories, creating global panic. Mozambique has witnessed the evolution of COVID-19 epidemic associated with the weakness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
2
4
0
Order By: Relevance
“…In agreement with these findings, a recent event of an Italian traveler returning from Mozambique, exported the Omicron variant into Italy [35,38]. Taken together, the results of this study, and that of others [28,34,37], suggest that SARS-CoV-2 variants were introduced, circulated, continued to evolve in Mozambique, and that lineages unique to Mozambique can potentially be disseminated to other countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with these findings, a recent event of an Italian traveler returning from Mozambique, exported the Omicron variant into Italy [35,38]. Taken together, the results of this study, and that of others [28,34,37], suggest that SARS-CoV-2 variants were introduced, circulated, continued to evolve in Mozambique, and that lineages unique to Mozambique can potentially be disseminated to other countries.…”
Section: Discussionsupporting
confidence: 88%
“…Despite these limitations, our analyses show that variants such as the C.1 and C1.1 lineages, and VOCs, such as Alpha, Beta, and Delta, were mostly introduced from South Africa during this study period. Previous investigations indicated initial introduction into Mozambique originated from European and North American travelers [34,37]. Notably, when travel restrictions were implemented during 2020, fewer introduction events were inferred.…”
Section: Discussionmentioning
confidence: 99%
“…In March–April, 2021, alpha was the dominating variant in Europe, absent in our dataset, while beta prevailed in South Africa and rapidly became dominant in Mozambique by February, 2021, 8 , 21 suggesting that international movement restrictions had little effect on stopping introductions into Mozambique from neighbouring countries. 8 , 13 Despite the international travel and tourism restrictions, some essential movements between Mozambique and South Africa were allowed (repatriations, transport of essential services or goods, medical needs). Additionally, regional trade in southern Africa returned to pre-pandemic levels by December, 2020, 21 and clandestine movement between neighbouring countries might also have been a source of introductions.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 11 , 12 To date, no studies have reported on SARS-CoV-2 genomic lineages in Mozambique and how, when, and from where they were initially introduced. 13 Importantly, identification and quantification of import and export events is highly conditioned by the dataset used to compare. Phylogenetic tools are now available to incorporate the entire deposited Global Initiative on Sharing Avian Influenza Data (GISAID) database, 14 which includes millions of SARS-CoV-2 sequences to evaluate and understand local epidemics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation